Effect of Vortex-Generator Planform and Height on the Trade-Off between Lift Enhancement and Wake Contraction around a Circular Cylinder - Karthik Jayanarasimhan; Navin Kumar Balasubramanian; Nagaraj Meenakshi Sundaram; M. Siva Sankari (Three E Science Institute, 2026)
Passive flow control of circular-cylinder wakes remains important because wake organizations govern aerodynamic loading, force fluctuations, and vortex-induced response. This study examines how vortex-generator (VG) planform and height affect lift behavior and near-wake structure around a circular cylinder. Triangular and ogival VGs with heights of 4, 7, and 10 mm were mounted at the cylinder apex and evaluated using three-dimensional transient URANS simulations with the SST k–ω model at Re = 53,000. Supporting wind-tunnel force measurements were also performed to assess whether the numerical trends were qualitatively reproduced experimentally. All VG-equipped configurations reduced the recirculation region, narrowed the wake, and decreased the centerline velocity deficit relative to the clean cylinder. Among the triangular cases, the 10 mm VG produced the strongest wake contraction, reducing the recirculation length from 1.35D to 0.70D. Among the ogival cases, the 10 mm VG generated the highest peak lift coefficient (approximately 1.45), although its wake contraction remained slightly weaker than that of the corresponding triangular configuration. These results show that the geometry yielding the strongest wake suppression is not identical to that giving the highest lift enhancement. The wind-tunnel measurements reproduced the overall ranking trends. However, because the experimental inflow conditions were not Reynolds-number matched to the numerical setup, the comparison is interpreted as qualitative trend support rather than strict validation. The results demonstrate that the VG planform and height jointly control the trade-off between wake contraction and lift enhancement.